(untitled) (Nigerian Journal of Physiological Sciences, 2025)
The study was aimed at providing a pattern of blood pressure decrease after an acute bout of exercise in normotensive subjects. A simple random sampling technique was used to select 138 apparently normotensive subjects (83 males and 55 females; age range 18-30 years), and the mean age was 22.28±0.52 and 19.84±0.28 in males and females, respectively. All participants were indigenes and undergraduate students of the University of Maiduguri, Borno State, Nigeria. The mean BMI was 23.29±3.80 kg/m and 19.07±2.42 kg/m in males and females, respectively. The mean resting SBP (118.65±1.52 and 105.6±2.14 in males and females, respectively), DBP (74.44±1.48 mmHg and 70.04±1.42 mmHg in males and females, respectively), and HR (83.92±2.63 bpm and 87.00±2.76 bpm in males and females, respectively) were recorded on their arrival. The mean SBP (145.28±2.67 mmHg and 123.64±1.97 mmHg in males and females, respectively), DBP (82.68±1.70 mmHg and 75.84±1.36 mmHg in males and females, respectively), and HR (112.96±3.08 bpm and 127.44±4.01 bpm in males and females, respectively) were recorded at 10 minutes of exercise. The study observed a significantly higher (p < 0.05) BMI in males than in females. Though BMI was positively associated with SBP at the end of 60 minutes into the recovery in males, the HR was negatively associated with BMI in females at 60 minutes into the exercise recovery. Meanwhile, such association was not seen in other parameters. The mean SBP, DBP, & HR at 10 minutes of exercise were all significantly higher (p < 0.05) than the resting state in both males and females. The decrease in the mean SBP, DBP, & HR after exercise was plotted against time for 60 minutes into the exercise recovery. A positive percentage change of SBP (22.56% and 17.18% in males and females, respectively), DBP (11.04% and 8.66% in males and females, respectively) and HR (34.41% and 45.37% in males and females, respectively) was seen at 10 minutes of exercise. A curvilinear pattern of SBP, DBP, and HR decline was observed at the end of 60 minutes. At the 3rd minute, the SBP in both males and females was already on baseline; DBP in males was slightly above baseline with a 2% positive change, while SBP in females was slightly below baseline. The SBP of male and female participants after the 3rd minute fell below baseline and remained persistently negative till the end of 60 minutes, with the female curve being far away from the baseline compared to male. The DBP in both males and females was on the baseline at the 14th and 15th minutes, respectively; the curve fell below baseline and remained persistent, but very close to the baseline. The curvilinear pattern of HR in both males and females showed a positive percentage but was above the baseline in both males and females. The study concluded that a typical curvilinear pattern of SBP crossed the baseline at the 3rd minute in both males and females, the magnitude of which is higher in females than in males; the DBP crosses at the 14th and 16th minutes and remained close to the baseline. Meanwhile, HR remained above the baseline. It is therefore suggested that SBP should be taken as a standard pattern for BP decrease during exercise.